Glyphosate exposures and kidney injury biomarkers in infants and young children. (January 2020) - Trasande, Leonardo; Aldana, Sandra India; Trachtman, Howard; Kannan, Kurunthachalam; Morrison, Deborah; Christakis, Dimitri A.; Whitlock, Kathryn; Messito, Mary Jo; Gross, Rachel S.; Karthikraj, Rajendiran; Sathyanarayana, Sheela
Abstract: The goal of this study was to assess biomarkers of exposure to glyphosate and assess potential associations with renal function in children. Glyphosate is used ubiquitously in agriculture worldwide. While previous studies have indicated that glyphosate may have nephrotoxic effects, few have examined potential effects on kidney function in children. We leveraged three cohorts across different phases of child development and measured urinary levels of glyphosate. We evaluated associations of glyphosate with three biomarkers of kidney injury: albuminuria (ACR), neutrophil gelatinase-associated lipocalin (NGAL), and kidney injury marker 1 (KIM-1). Multivariable regression analyses examined associations of glyphosate with kidney injury biomarkers controlling for covariates. We identified glyphosate in 11.1% of the total participants. The herbicide was detected more frequently in the neonate population (30%). Multivariable regression models failed to identify significant associations of log-transformed glyphosate with any of the kidney injury biomarkers, controlling for covariates age, sex, and maternal education. While we confirm detectability of glyphosate in children's urine at various ages and stages of life, there is no evidence in this study for renal injury in children exposed to low levels of glyphosate. Further studies of larger sample size are indicated to better understand putative deleterious effects of the herbicide after different levels of exposure. Graphical abstract: Image 1 Highlights: We measured urinary levels of glyphosate in three pediatric cohorts and evaluated associations with kidney injury. We identified glyphosate in 11.1% of the participants, more frequently in neonates (30%). There was no association between glyphosate exposure and any kidney injury molecules. Abstract : Glyphosate is detectable is the urine of 11% of infants and young children (30% of neonates). However, there is no association with albuminuria or biomarkers of renal tubular injury.